2005
DOI: 10.1264/jsme2.20.151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Bacterial Community in 3-Chlorobenzoate-Contaminated Soil by PCR-DGGE Targeting the 16S rRNA Gene and Benzoate 1,2-Dioxygenase Gene (benA)

Abstract: We analyzed the changes that occurred in a bacterial community from forest soil after adding 3-chlorobenzoate (3CB) by two different PCR-denaturing gradient gel electrophoreses (DGGEs), targeting the 16S rRNA gene and benA encoding the benzoate 1,2-dioxygenase large subunit. The concentration of 3CB in the soil had decreased to about 40% of that added (500 ppm) after seven days at 28C. Total DNA was directly extracted from the soil before and after incubation, and subjected to PCR-DGGE. Four new bands clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The application of molecular biological methods has greatly facilitated the study of natural bacterial communities and the identification of functionally significant organisms within them 27,31) . In this study, we confirmed the existence of NFB isolated from root and starch of sago palm in natural samples by comparing banding patterns from denaturing gradient gel electrophoresis (DGGE) targeted at nifH between the isolates and community DNA extracted from root and starch samples.…”
mentioning
confidence: 99%
“…The application of molecular biological methods has greatly facilitated the study of natural bacterial communities and the identification of functionally significant organisms within them 27,31) . In this study, we confirmed the existence of NFB isolated from root and starch of sago palm in natural samples by comparing banding patterns from denaturing gradient gel electrophoresis (DGGE) targeted at nifH between the isolates and community DNA extracted from root and starch samples.…”
mentioning
confidence: 99%
“…Sakai et al (138) reported that the Burkholderia cepacia RASC type 2,4-D-degrading genes harbored on large plasmids spread out among 2,4-D-degrading bacteria isolated from soil in Japan. A soil bacterial community capable of degrading 3-chlorobenzoate was characterized by 16S rRNA and benA gene-targeted PCR-DGGE (112,113). The bacterial community diversity of anaerobic fluidized bed bioreactors treating some aromatic compounds, such as phenol (15) and 2,4-dinitroaniaole (7), was studied.…”
Section: Biodegradation Of Hazardous Chemicals: One Of the Fastest Grmentioning
confidence: 99%
“…Moreover, traditional culture-dependent techniques are of limited use for the analysis of microbial assemblages, since more than 90% of indigenous microorganisms in nature are not culturable under laboratory conditions (Amann et al, 1995). In recent years, various culture-independent methods such as phospholipid fatty acid analysis (PLFA) and 16S rRNA gene directed Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) have been useful for detecting pollutant-induced changes in the composition of natural microbial communities (Morimoto et al, 2005;Chinalia and Killham, 2006;Ratcliff et al, 2006). PLFA results are interpreted based on the assumption that phospholipids make up a relatively constant proportion of the cell biomass and that variation in fatty acids among taxonomic groups can be used as biomarkers and the PLFA pattern of an environmental sample therefore reflects the microbial community composition (White et al, 1996;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%